Emerging Geospatial Technologies in Environmental Research, Education, and Outreach - Sergio Bernardes; Margueritte Madden; Ashurst Walker; Andrew Knight; Nicholas Neel; Akshay Mendki; Dhaval Bhanderi; Andrew Guest; Shannon Healy; Thomas Jordan (Department of Geography Education, University of Jember, 2020)
Drawing on the historical importance of visual interpretation for image understanding and knowledge discovery, emerging technologies in geovisualization are incorporated into research, education and outreach at the Center for Geospatial Research (CGR) in the Department of Geography at the University of Georgia (UGA), USA. This study aimed to develop the 3D Immersion and Geovisualization (3DIG) system consisting of uncrewed aerial systems (UAS) for data acquisition, augmented and virtual reality headsets and mobile devices, an augmented reality digital sandbox, and a video wall. We were working together integrated data products from the UAS imagery, including digital image mosaics and 3D models, and readily available gaming engine software to create augmented and virtual reality immersive visualizations. The use of 3DIG in research is demonstrated in a case study documenting the seasonal growth of vegetables in small gardens with a time series of 3D crop models generated from UAS imagery and Structure from Motion photogrammetry. Demonstrations of 3DIG in geography and geology courses, as well as public events, also indicate the benefits of emerging geospatial technologies for creating active learning environments and fostering participatory community engagement. Keywords: Environmental Education; Geovisualization; Augmented Reality; Virtual Reality; UAS, Photogrammetry Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License